High-dose immunosuppressive therapy with PBPC support in the treatment of poor risk multiple sclerosis - Kozák, T; Havrdová, E; Pit'ha, J; Gregora, E; Pytlík, R; Maaloufová, J; Marecková, H; Kobylka, P; Vodvárková, S (Bone marrow transplantation, 2000)
High-dose immunoablative chemotherapy with autologous haematopoietic cell support might be beneficial in the treatment of intractable forms of MS. We mobilised PBPC in 11 patients with secondary progressive MS and finally eight patients were grafted after high-dose BEAM chemotherapy with either in vitro or in vivo T cell depletion. Median EDSS and SNRS scores at the time of inclusion were 6.5 (6.5-7.5) and 56 (44-65), respectively. PBPC mobilisation was safe with no serious adverse effects, and without significant aggravation of disability. One patient improved significantly (by 1.0 point on EDSS) after the mobilisation. Two mobilisation failures were observed. No life-threatening events occurred during the transplantation. All grafted patients, except one, at least stabilised their disability status. One patient improved significantly (by 1.5 points on EDSS), two patients improved slightly (by 0.5 points on EDSS), one patient worsened by 1.0 point on the EDSS in 10 months. Improvement occurred with a delay of 2-4 months. Median EDSS and SNRS of grafted patients at the last follow up were 6.5 (5.5-8.5) and 64 (39-73), respectively with median follow-up of 8.5 months. Further follow-up is needed to determine the disease course after complete immune reconstitution. Bone Marrow Transplantation (2000) 25, 525-531.
Keywords: Immunosuppressive Agents; leukaferéza; podskupiny lymfocytů; neutropenie; stupeň závažnosti nemoci; přežívání štěpu; Cytarabine; Neutropenia; roztroušená skleróza; Leukapheresis; Prognosis; mladiství; Middle Aged; mužské pohlaví; karmustin; CD4-CD8 Ratio; Graft Survival; Lymphocyte Subsets; Adult; mobilizace hematopoetických kmenových buněk; poměr CD4 a CD8 lymfocytů; Follow-Up Studies; infekce; magnetická rezonanční tomografie; Multiple Sclerosis; následné studie; Carmustine; Melphalan; Hematopoietic Stem Cell Transplantation; Magnetic Resonance Imaging; ženské pohlaví; prognóza; transplantace hematopoetických kmenových buněk; imunosupresiva; Humans; horečka; cytarabin; melfalan; Antigens, CD; Etoposide; Infections; Severity of Illness Index; etoposid; lidé středního věku; Fever; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Hematopoietic Stem Cell Mobilization; Adolescent; CD antigeny; lidé; Male